2004
DOI: 10.1101/gad.285504
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-dependent activation of the transcription factor TIF-IA links rRNA synthesis to nutrient availability

Abstract: In cycling cells, transcription of ribosomal RNA genes by RNA polymerase I (Pol I) is tightly coordinated with cell growth. Here, we show that the mammalian target of rapamycin (mTOR) regulates Pol I transcription by modulating the activity of TIF-IA, a regulatory factor that senses nutrient and growth-factor availability. Inhibition of mTOR signaling by rapamycin inactivates TIF-IA and impairs transcription-initiation complex formation. Moreover, rapamycin treatment leads to translocation of TIF-IA into the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
394
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(420 citation statements)
references
References 52 publications
17
394
0
4
Order By: Relevance
“…In support, previous data have indicated that c-Myc mRNA and protein are readily altered in young humans and animals after muscle contraction or stretch (1,52). Not only can mTOR affect translation initiation and elongation, but it can also influence mRNA expression, particularly genes associated with ribosomal assembly (26,42,50). Using reporter gene activity, Teleman et al (50) found that cMyc, a regulator of ribosome biosynthesis, was a downstream target of mTOR and is upregulated in the presence of insulin and downregulated in response to rapamycin.…”
Section: Discussionsupporting
confidence: 74%
“…In support, previous data have indicated that c-Myc mRNA and protein are readily altered in young humans and animals after muscle contraction or stretch (1,52). Not only can mTOR affect translation initiation and elongation, but it can also influence mRNA expression, particularly genes associated with ribosomal assembly (26,42,50). Using reporter gene activity, Teleman et al (50) found that cMyc, a regulator of ribosome biosynthesis, was a downstream target of mTOR and is upregulated in the presence of insulin and downregulated in response to rapamycin.…”
Section: Discussionsupporting
confidence: 74%
“…), or a substitution mutant (S199D). The substitution of an acidic residue for the serine at 199 has been reported previously to inhibit the ability of Rrn3 to interact with both SL1and RNA polymerase I (43). The data presented in lanes 6 and 7 of Fig.…”
Section: Dna Binding By Rrn3 Is Independent Of Its Ability To Interacsupporting
confidence: 56%
“…[9][10][11], and has been shown to be a prime target for the regulation of the Pol I activity. 8,12,13 To interfere with these mechanisms, we constructed a yeast strain, named CARA (for Constitutive Association of Rrn3 and A43), in which the endogenous, essential Rrn3 factor and the A43 subunit of the Pol I that interacts with Rrn3, 14 were supplied as an Rrn3-A43 fusion protein. 1 The chimeric construct assembled properly within Pol I and formed a constitutively active, non dissociable Pol I-Rrn3 complex.…”
Section: The Cara Strain or How To Make Pol I Transcription Constitumentioning
confidence: 99%